2019
DOI: 10.1007/s13349-019-00361-8
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of the Milan Cathedral: dynamic characteristics and vibration-based SHM

Abstract: The traditional collaboration between Politecnico di Milano and Veneranda Fabbrica del Duomo di Milano  the historic Institution established by Gian Galeazzo Visconti in 1387 and having in charge all operational aspects related to the Milan Cathedral since more than 600 years  recently focused on the design and installation of a structural monitoring system, with the objective of assisting the condition-based structural maintenance of the historic church through the continuous interrogation of sensors instal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In fact, as pointed out in the previous sections, several longterm ambient vibrations campaigns have demonstrated that the natural frequencies of monumental masonry buildings are influenced by environmental factors such as temperature, humidity, etc. (Ramos et al, 2010;Saisi et al, 2015;Gentile et al, 2016Gentile et al, , 2019Ubertini et al, 2016Ubertini et al, , 2017Baraccani et al, 2017;Masciotta et al, 2017;Tsogka et al, 2017;Barsocchi et al, 2019). In particular, for masonry towers the amplitudes of natural frequencies are increasing functions of temperature, and for the structures monitored in Saisi et al (2015) and Azzara et al (2018) their relative yearly differences are on the order of 5%.…”
Section: Non-linear Fe Modeling and Experimental Resultsmentioning
confidence: 99%
“…In fact, as pointed out in the previous sections, several longterm ambient vibrations campaigns have demonstrated that the natural frequencies of monumental masonry buildings are influenced by environmental factors such as temperature, humidity, etc. (Ramos et al, 2010;Saisi et al, 2015;Gentile et al, 2016Gentile et al, , 2019Ubertini et al, 2016Ubertini et al, , 2017Baraccani et al, 2017;Masciotta et al, 2017;Tsogka et al, 2017;Barsocchi et al, 2019). In particular, for masonry towers the amplitudes of natural frequencies are increasing functions of temperature, and for the structures monitored in Saisi et al (2015) and Azzara et al (2018) their relative yearly differences are on the order of 5%.…”
Section: Non-linear Fe Modeling and Experimental Resultsmentioning
confidence: 99%
“…Another structure with a static and dynamic monitoring system is the Milan Cathedral [13]. The structure was built from 1386 to 1765, and it is a mix of Gothic style and regional Lombardy style, where also neo-classic, neo-gothic.…”
Section: Ambient Vibration Testmentioning
confidence: 99%
“…[6]. Examples of recent structural monitoring studies in the Italian architectural heritage include: the Consoli Palace in Gubbio [7], the church of Santa Maria in Collemaggio in L'Aquila [8], the San Pietro belltower in Perugia [9], the Milan Cathedral [10], the San Vittore bell-tower in Arcisate [11], and the Rubbianello Bridge [12]. This paper adds to the above list and presents the first results from a structural monitoring system installed in the quadriporticus of the Ducal Palace in Camerino, within the field activities planned in the European research project named ARCH (Advancing resilience of historic areas against climate-related and other hazards -https://savingculturalheritage.eu/) funded in the Horizon 2020 framework for the years 2019-2022.…”
Section: Introductionmentioning
confidence: 99%